Sociometrics and human relationships : analyzing social networks to manage brands, predict trends, and improve organizational performance - Gloor, Peter A. 1961- (Emerald Publishing Limited, 2017)
Sociometrics and Human Relationships translates the latest academic research into practical business strategies and techniques as well as actionable insights, providing a wealth of examples for social network analysis and predicting trends. Gloor illustrates how to improve organizational performance by optimizing communication and collaboration through email. Based on Collaborative Innovation Networks courses which have been taught for over a decade to students forming virtual teams across a number of universities, Gloor shows readers how to leverage virtual collaborative creativity in the Internet age, and helps them understand and apply the dynamics of online communication via a variety of tools. Gloor has also created a tool that analyses all types of social media such as: Twitter, Wikipedia, online blogs and Facebook as well as email or Skype logs to predict election outcomes, perception and strength of brands, customer and employment satisfaction, or fraudulent behavior. Gloor explains how to use his tool, Condor, to visualize, monitor and manage brands, products and topics online, as well as analyzing organizations through their email networks.- Resumé vydavatel